2017
DOI: 10.1021/acs.jpcc.7b10147
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Oxygen-Based Electrochemical Reactions through Spin Orientation

Abstract: The role of spin orientation on the reactivity of oxygen reduction reaction (ORR) intermediates (O, OH) on a ferromagnetic electrode surface is studied using constrained density functional theory formalism. We show that the strength of the binding of these reaction intermediates depend on their relative spin orientations with respect to the magnetization of the electrode. This suggests that oxygen-based electrochemical reactions on ferromagnetic catalyst surfaces can be controlled through the applied magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Strongly correlated itinerant electrons in FM domains have a profound impact in catalysis, and they add spin-polarization to the thermodynamics. Bhattacharjee and Lee observed spin-polarized oxygen atoms adsorbed on the FM PdFe alloy and controlled oxygen reduction through the spin orientation . The same authors reported a nonlinear trend in NH 3 adsorption energy on FM metals .…”
Section: Theoretical Revisionmentioning
confidence: 88%
See 1 more Smart Citation
“…Strongly correlated itinerant electrons in FM domains have a profound impact in catalysis, and they add spin-polarization to the thermodynamics. Bhattacharjee and Lee observed spin-polarized oxygen atoms adsorbed on the FM PdFe alloy and controlled oxygen reduction through the spin orientation . The same authors reported a nonlinear trend in NH 3 adsorption energy on FM metals .…”
Section: Theoretical Revisionmentioning
confidence: 88%
“…Similar deviations due to magnetism are ubiquitously observed in pure 3d metals, , intermetallic alloys, carbides, oxides, , sulfides, and nitrides involved in different chemical transformations. The spin of the electron is a crucial factor to be considered in catalysis. The alternation of the spin structure of the transition metals changes the adsorption/desorption energy of the active sites, Figure a, dramatically affecting the reaction thermodynamics. ,, …”
Section: Introductionmentioning
confidence: 99%
“…31−33 Even under extreme conditions, such as Ni electrodeposition across ferromagnetic nanocontacts, 34 with field gradients ∇B ∼ 10 7 T m −1 , the field gradient force alters the deposition rate by inducing localized convection, thereby changing the Ni 2+ concentration at the electrode, rather than by a shift of the intrinsic kinetics. Furthermore, new spin-orientation-dependent overpotentials predicted 35,36 and observed in water splitting 37−39 have also shown no change in kinetics.…”
Section: = ×mentioning
confidence: 95%
“…As the double layer is hidden deep inside any diffusion layer or hydrodynamic boundary layer, and the magnetic energy of a paramagnetic ion in a 1 T field is 5 orders of magnitude lower than k B T , there has been a general consensus that both the double layer and the underlying reaction kinetics are insensitive to magnetic fields. Even under extreme conditions, such as Ni electrodeposition across ferromagnetic nanocontacts, with field gradients ∇ B ∼ 10 7 T m –1 , the field gradient force alters the deposition rate by inducing localized convection, thereby changing the Ni 2+ concentration at the electrode, rather than by a shift of the intrinsic kinetics. Furthermore, new spin-orientation-dependent overpotentials predicted , and observed in water splitting have also shown no change in kinetics.…”
Section: Introductionmentioning
confidence: 91%
“…The concept of spin selectivity effect can be traced back to the pioneering discovery in 1999 that chiral molecules can be used as the filter of electron spin orientation . It allows the preferential spin orientation of electrons to be transmitted through chiral materials, and this specific transport is called chiral-induced spin selectivity (CISS). Notably, the CISS catalysts have been proved to have glorious electrocatalytic activity. Relevant experiments in oxygen-involved reactions have demonstrated that the CISS effect can effectively inhibit the formation of H 2 O 2 by controlling the intermediates on the catalyst surface to arrange in a spin parallel manner (OH↑ × ↑OH), and theoretical study of ferromagnetic electrode also shows a spin selectivity effect. Similarly, the magnetic field has also been confirmed to have a significant effect on spin selectivity in electrocatalytic reactions, including two aspects as shown in Figure . Electrocatalytic reactions usually involve the combination of spin-related free radical pairs, singlet (↑↓) or triplet states (↑↑).…”
Section: Possible Mechanisms Of Magnetic Field-enhanced Electrochemic...mentioning
confidence: 99%